Aplikasi Energi Alternatif Sinar Matahari Pada Mesin Pelontar Pakan Ikan Mandiri Berbasis Microcontroller - Tohari, M. lutfi Nur; Istiqlaliyah, Hesti (Jurnal Mesin Nusantara, 2022)
The sun is one source of renewable energy that is unlimited and always available, this energy can be converted into electrical energy by utilizing solar panels. Sunlight in Indonesia has great potential to be used as a solar power plant (PLTS), sunlight is an alternative energy with an average radiation of 4.5-4.8 kWh/m2. cell module, with 15% cell conversion efficiency. Automatic fish feeding methods have been developed a lot, but most of the automatic fish feed still uses electricity from PLN, which will be an obstacle in the event of a power outage from PLN. In this study, we tested a solar power generation system (PLTS) that will be used to charge a battery that is used as a power source for a self-sustaining fish feed launcher using a solar tracker as an angle changer of solar panels that can follow sunlight. The test results of the device can work well and can produce stable charging power with an average charging power of 30.61 watts and the highest charging current of 2.5A, with the highest battery charging efficiency of 74%.